2015
DOI: 10.1016/j.spinee.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation model analysis of the length-of-hospital stay after lumbar spine surgery

Abstract: Background context Length of hospital stay (LOS) after lumbar spine surgery (LSS) can be affected by many factors. However, few studies have evaluated predictors of LOS, and all have used limited number of variables as predictors. Purpose To identify pre-surgical, surgical, and post-surgical predictors of LOS following LSS. Study Design/Setting Retrospective review of consecutive patients who had LSS at the (Blinded) Hospital from October, 2008 to April, 2012. Patient Sample 593 patients who underwent LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
2
27
0
2
Order By: Relevance
“…The M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 average length of stay for patients with a post-operative complication was 5.1 ±2.3 days vs 2.9 ±0.9 days for patients with no complications (p<0.001). These findings are in keeping with Kanaan et al [37] who carried out a retrospective review of 593 patients who had had laminotomy, laminectomy or arthrodesis at a US hospital. Using a structural equation model for their analysis, they found an average length of stay of 4.01 (±2.73) days, with postsurgical factors relating to the patient's function again predicting the highest variation in LOS.…”
Section: Eras In Major Spinal Surgerysupporting
confidence: 87%
See 1 more Smart Citation
“…The M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 average length of stay for patients with a post-operative complication was 5.1 ±2.3 days vs 2.9 ±0.9 days for patients with no complications (p<0.001). These findings are in keeping with Kanaan et al [37] who carried out a retrospective review of 593 patients who had had laminotomy, laminectomy or arthrodesis at a US hospital. Using a structural equation model for their analysis, they found an average length of stay of 4.01 (±2.73) days, with postsurgical factors relating to the patient's function again predicting the highest variation in LOS.…”
Section: Eras In Major Spinal Surgerysupporting
confidence: 87%
“…Surgical complexity can lead to an increased LOS however work by Gruskay et al (36] and Kanaan et al [37] suggest that there is scope to reduce LOS. In the study by Gruskay et al [36] in 103 patients undergoing elective, open, one to three level posterior lumbar instrumented fusion (with or without decompression) they found that intraoperative events did not affect length of stay, whilst potentially modifiable post-operative events did.…”
Section: Eras In Major Spinal Surgerymentioning
confidence: 99%
“…First, all participants who volunteered for this study were younger than 50 yr, whereas back surgery is most common in patients at least 60 yr old. 18 The ability to discriminate between muscle bodies may prove more difficult with aging due to relative atrophy or anatomic changes of the spine itself. Furthermore, no participant had prior surgery in the lumbar spine, so we cannot comment on the efficacy of this technique in patients who have had prior back surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports in the literature regarding the predictive value of age for LOS following lumbar fusion. [ 12 9 6 1 ] One theory is that advanced age may be associated with a higher complication rate postoperatively, thus increasing LOS. [ 11 ] However, even this theory has been challenged in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Chief among these may be patient function and walking distance. [ 6 ] There is the possibility that combining the effect of more than one variable could have a greater impact on hospital stay. The current study was done to focus the study on the three most commonly investigated and debated factors regarding LOS, and we believe convincingly shows that they only have a minor association with LOS.…”
Section: Discussionmentioning
confidence: 99%